Effect of pioglitazone on body composition and bone density in subjects with prediabetes in the ACT NOW trial. Issue 10 (7th May 2013) - Bray, G. A.; Smith, S. R.; Banerji, M. A.; Tripathy, D.; Clement, S. C.; Buchanan, T. A.; Henry, R. R.; Kitabchi, A. E.; Mudaliar, S.; Musi, N.; Ratner, R. E.; Schwenke, D. C.; et al.
Abstract : Aims: This study examined the effects of pioglitazone on body weight and bone mineral density (BMD) prospectively in patients with impaired glucose tolerance as pioglitazone (TZD) increases body weight and body fat in diabetic patients and increases the risk of bone fractures. Methods: A total of 71 men and 163 women aged 49.3 (10.7) years [mean (s.d.)]; body mass index (BMI), 34.5 (5.9) kg/m 2 were recruited at five sites for measurements of body composition by dual energy X‐ray absorptiometry at baseline and at conversion to diabetes or study end, if they had not converted. Results: Mean follow‐up was 33.6 months in the pioglitazone group and 32.1 months in the placebo group. Body weight increased 4.63 ± 0.60 (m ± s.e.) kg in the pioglitazone group compared to 0.98 ± 0.62 kg in the PIO group (p < 0.0001). Body fat rose 4.89 ± 0.42 kg in the pioglitazone group compared to 1.41 ± 0.44 kg, (p < 0.0001) in placebo‐treated subjects. The increase in fat was greater in legs and trunk than in the arms. BMD was higher in all regions in men and significantly so in most. PIO decreased BMD significantly in the pelvis in men and women, decreased BMD in the thoracic spine and ribs of women and the lumbar spine and legs of men. Bone mineral content also decreased significantly in arms, legs, trunk and in the total body. Conclusions: Pioglitazone increased peripheral fat more than truncal fat and decreased BMD in several regions of the body.